Feasibility of implementing current best clinical practice for people who are using anabolic androgenic steroids within a Swiss primary care practice: a quality assurance study - Raphael Magnolini; Kuvinda Kossinna; Daniel Bjasch; Muriel Kruijver; Philip Bruggmann; Oliver Senn (Swiss Medical Weekly)
BACKGROUND: The non-medical use of anabolic androgenic steroids for the improvement of aesthetic and sports performance purposes has become a global substance use disorder, particularly among men in recreational sports. Health outcomes among people who are using anabolic androgenic steroids may be detrimental, yet healthcare services for these users are scarce. Therefore, the aim of this project was to conduct a quality assurance study to evaluate the feasibility of providing current best clinical practice for anabolic androgenic steroids users based on the published literature within a primary care practice in Zurich (Switzerland).